Survival of probiotic microorganisms in the gastrointestinal tract of experimental animals - I. V. Darmov; I. Yu. Chicherin; I. P. Pogorelsky; I. A. Lundovskikh; E. A. Durnev (Журнал инфектологии)
Development of methodology for the identification of certified probiotic microorganisms in the intestinal contents of white mice and uinea pigs and study of their survival in the gastrointestinal tract of experimental animals. Rifampicin-resistant bifidobacteria and lactobacilli were used in the experiments. Cultures of microorganisms that have retained the species features were administered orally for 14 days and the number of viable bifidobacteria and lactobacilli were determined by sowing of feces in a dense nutrient medium with rifampicin. Probiotic microorganisms administered orally to experimental animals for 14 days are detected in the feces on the second day of the experiment. Live probiotic bacteria ceases completely to be detected in the feces of animals 3 days after the termination of their oral administration. Using the developed universal method of differentiation of probiotic microorganisms entering the living organisms and strains of their own intestinal microflora a significant decrease (4–7 orders of magnitude) in survival of bifidobacteria and lactobacilli in the organisms of experimental animals was shown, followed by a lack of probiotic effect.